THE PROFILE OF COMMUNICATION STRATEGIES USED BY JUNIOR HIGH SCHOOL ENGLISH TEACHERS IN TEACHING AND LEARNING PROCESS IN SMP NEGERI 2 SUKAWATI - TRIANA JULIARI, I GUSTI AYU INDAH (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2016)
AbstractThis study is aimed at describing Communication Strategies used by Junior High School English teachers in SMP N 2 Sukawati. It includes kinds of Communication Strategies, the reasons of the use of Communication Strategies and the studentsâ?? perception toward Communication Strategies used by the teachers. The subjects of this study were Junior High School English teachers of the seventh and eighth grades of SMP Negeri 2 Sukawati. The data were collected by using some instruments namely observation sheet, questionnaire and interview guide. The kinds of Communication Strategies were gathered by observing and recording the teacher during teaching and learning process, while the questionnaire was used to investigate the studentsâ?? perception toward the Communication Strategies used by the teachers. The results of this study showed that there were 14 kinds of Communication Strategies used by the teachers. Code switching strategy was the most frequently used by the teachers. It occurred for 35 times in teaching and learning process. The reasons of the teachers used those strategies were to improve the studentsâ?? speaking abilities during teaching and learning process, and made them understood the material. The data also showed that the teachers got positive perception from their students in applying Communication Strategies during teaching and learning process.Keywords: Communication Strategies, English teacher, teaching and learning processÂ